Peran Guru BK dalam Membentuk Sikap Disiplin Siswa Melalui Layanan Konseling Kelompok di SMP Negeri 5 Kupang - Fallo, Gabriela Angelica; Rohi, Enasely Mega Wenyi (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
Discipline is a central determinant of classroom order and learning effectiveness, yet schools still face recurrent issues such as lateness, absenteeism, minor rule violations, and weak time management. This study describes the role of Guidance and Counseling (GC) teachers in shaping students’ disciplinary attitudes at SMP Negeri 5 Kupang through group counseling services. Using a qualitative descriptive, single-case study design, data were collected via guided observation of four group sessions, semi-structured interviews with a GC teacher, a homeroom teacher, and eight students, and document analysis (school rules, attendance logs, service notes). Data were analyzed using the Miles and Huberman flow (data reduction, display, verification) with source/method triangulation and brief member checking. Findings indicate that the GC teacher acts as facilitator, counselor, educator, and coordinator, integrating preventive, curative, preservative, and developmental functions. Group counseling augmented with self-management techniques (goal setting, self-monitoring, self-reinforcement) and school–parent collaboration fosters punctuality, rule compliance, and task management. Positive reinforcement paired with proportionate consequences and routine progress reviews supports habit formation. Practical implications highlight the need for needs-based planning, integration of GC timetables into the academic calendar, standardized self-monitoring tools, and ongoing formative evaluation to sustain behavioral change.